A study on the reliability of bilispect to measure bilirubin levels in term neonates - Tengku Hussain, Tengku Hasnita (2015)
INTRODUCTION : Neonatal jaundice commonly occurred in newborn babies. The monitoring of it becomes very important to prevent complications. Blood taking is an invasive procedure that associated with pain in newborn. Availability of new devices with updated technology leading to non invasive monitoring in newborn. Development of Bilispect as transcutaneous bilirubinometer gave opportunities to reduce blood taking in newborn. OBJECTIVES: To test reliability of Bilispect in monitoring bilirubin level of term babies, pre and post-phototherapy. METHODS: This study was a cross sectional study in HUSM for term babies with neonatal jaundice who fulfilled inclusion criteria. RESULT: There were total of 74 babies involved in this study. Among these, 44 babies involved in both part pre-phototherapy and post-phototherapy reading. Additional of 15 babies only involved in one part of the study, either pre-phototherapy or post-phototherapy. Total of 59 samples were collected in each part. The gender distribution was equal for pre and post-phototherapy group. The mean age was 3.9 days with mean gestation was 39weeks. The differences of serum bilirubin and Bilispect reading for pre-phototherapy result was from -132.6 to 190.8. For the post-phototherapy result, the differences value range from -45.2 to 164.0. Pearson correlation value derived were weak positive correlation (0.466) and moderate positive correlation (0.566) for pre and post-phototherapy respectively. The Bland Altman plot degree of agreement between these methods were 93.22% for prephototherapy and 96.6% for post-phototherapy. CONCLUSION: The results of this study showed that the Bilispect device had a statistically significant correlation with the serum bilirubin values. However for too many samples the differences between the two were too big to support clinical usage of the Bilispect at this point in time. In conclusion serum bilirubin is still a gold standard for jaundice monitoring in newborn.